2023
DOI: 10.1093/humrep/dead196
|View full text |Cite
|
Sign up to set email alerts
|

The humanin analogue (HNG) alleviates intrauterine adhesions by inhibiting endometrial epithelial cells ferroptosis: a rat model-based study

Liping Zou,
Jin Huang,
Qiaoling Zhang
et al.

Abstract: STUDY QUESTION Does a humanin analogue (HNG) have a therapeutic effect on intrauterine adhesions (IUAs) caused by uterine cavity surgery in a rat model? SUMMARY ANSWER HNG supplementation attenuated the development of endometrial fibrosis and IUAs, improved fertility, and contributed to the regulation of endometrial fibrosis by inhibiting endometrial ferroptosis in rats with IUAs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…We and other authors previously reported that ferroptosis occurred in the injured endometria to promote endometrial fibrosis in IUA [ 10 , 11 ]. Ferroptosis is a novel form of oxidative cell death, which is regulated by glutathione peroxidase 4 (GPX4) and caused by iron-dependent oxidative damage [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 94%
“…We and other authors previously reported that ferroptosis occurred in the injured endometria to promote endometrial fibrosis in IUA [ 10 , 11 ]. Ferroptosis is a novel form of oxidative cell death, which is regulated by glutathione peroxidase 4 (GPX4) and caused by iron-dependent oxidative damage [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 94%